IMPACT OF LEADERSHIP QUALITIES ON SPORTS PARTICIPATION AMONG UNIVERSITY ATHLETES OF LAHORE - Kalsoom Najam (PUPIL: International Journal of Teaching, Education and Learning, 2026)
The research intends to focus on the perception of players regarding the impact of leadership qualities on the sports participation among university athletes. The purpose of this research was to investigate that how the dimensions of leadership behavior can help in increasing the sports participation of university athletes. By applying the simple random sampling and using survey methodology, a total of 214 university athletes (male/female) was selected. These athletes belong to sports sciences departments of different universities of Lahore. For this study, adapted questionnaires of Leadership Scale for Sports Guidance Scale (LSS) developed by Chelladurai & Saleh (1990) and Sports Participation questionnaire ‘Ungt folk a Islandi (2010) have been used to get the opinion of the participants. Results of the study demonstrated that there is a positive relationship of training and instruction, democratic behavior and positive feedback with sports participation of university athletes. Whereas autocratic behavior and social support were found to be non-significantly associated with sports participation. Through the reliability analysis, it can observe that data is reliable as in case of the variables, Training and Instruction, Democratic Behavior, Autocratic Behavior, Social Support, and Positive Feedback, Cronbach alpha value is, .84,.72,.71,.68 and .79 respectively. On the basis of results, it can be said that designed hypotheses of this research have been proved. However, the regression analysis shows that the relationship of sports participation with the dependent variables is significantly positive, whereas the relationship between variables autocratic behavior and social support with sports participation is slightly positive. Overall this study can be concluded that leadership qualities promote all type of positive participation in sports persons and individuals.